Kajian Struktur Dan Nilai Moral Pada Novel Rapijali 1mencari Karya Dee Lestari Sebagai Pembelajaran Bahasa Indonesia Di SMA - Fermadi, Dodi (Universitas Mathla'ul Anwar Banten, 2025)
This research aims to determine the structure and moral values contained in the novel Rapijali 1 Looking for Dee Selukis' work. The object of this research is the novel entitled Rapjali 1 Looking for, which contains 368 pages and was published by Pantabli Library in Yogyakarta in2021. The background of this research is the novel Rapjali 1 Looking for Dee Lestari's work which is very effective for studying structure and moral values, and is very good if used as teaching material in high school. The purpose of this research is to determine the structure andmoral values in the novel Rapijali 1 Mencari by Dee lestari as Indonesian language learning material in high school. The research method used is qualitative description, the data to be studied is the novel Rapijali 1 Mencari by Dee lestari. This research using qualitative descriptionmethods aims to examine moral structures and values. There are several books and journals to provide data to clarify research. The technique for collecting data uses documentation techniques.When reviewing the data to be researched, use a content study to describe it carefully and in a focused manner.The results of the research show that the study of the structure and moral values contained in the novel Rapijali 1 is looking for the work of Dee lestarithe building structure is the theme, namely Identity and the Search for True Self, setting: time setting,place setting, and socio-cultural background, Plot: initial stage, middle stage, and final stageCharacters: Ping, Oding, Yuda Alexander, Inggil, Jemima, Rakai, Lodeh, Buto. Point of ViewThird person limited moral values: Human relationships with God, human relationships with themselves, and human relationships with other humans in the social sphere.